Exploring Infant Fall Events Using Online Parenting Discussion Forums: Infodemiology Study - Nipuna Cooray; Si Louise Sun; Susan Adams; Lisa Keay; Natasha Nassar; Julie Brown (JMIR Publications, 2022)
BackgroundFalls represent the most common mechanism of injury requiring hospitalization among children under 12 months, and they commonly result in traumatic brain injury. Epidemiological studies exploring infant falls demonstrate the experienced burden, but they lack contextual information vital to the development of preventive interventions. ObjectiveThe objective of this study was to examine contextual information for falls involving children under 12 months, using online parenting discussion forums. MethodsOnline parenting forums provide an unobtrusive rich data source for collecting detailed information about fall events. Relevant discussions related to fall incidents were identified and downloaded using site-specific Google Search queries and a programming script. A qualitative descriptive approach was used to analyze the incidents and categorize contextual information into "precursor events" and "influencing factors" for infant falls. ResultsWe identified 461 infant fall incidents. Common fall mechanisms included falls from furniture, falls when being carried or supported by someone, falls from baby products, and falls on the same level. Across the spectrum of fall mechanisms, common precursor events were infant rolling off, infant being alone on furniture, product misuse, caretaker falling asleep while holding the infant, and caretaker tripping/slipping while carrying the infant. Common influencing factors were infant's rapid motor development, lapses in caretaker attention, and trip hazards. ConclusionsThe findings define targets for interventions to prevent infant falls and suggest that the most viable intervention approach may be to target parental behavior change. Online forums can provide rich information critical for preventive interventions aimed at changing behavior.